2015
DOI: 10.1371/journal.pone.0122377
|View full text |Cite
|
Sign up to set email alerts
|

Intrapericardial Administration of Mesenchymal Stem Cells in a Large Animal Model: A Bio-Distribution Analysis

Abstract: The appropriate administration route for cardiovascular cell therapy is essential to ensure the viability, proliferative potential, homing capacity and implantation of transferred cells. At the present, the intrapericardial administration of pharmacological agents is considered an efficient method for the treatment of cardiovascular diseases. However, only a few reports have addressed the question whether the intrapericardial delivery of Mesenchymal Stem Cells (MSCs) could be an optimal administration route. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 41 publications
4
35
0
Order By: Relevance
“…However, the feasibility of the concept is in line with other recent studies, in which myocardial homing of intrapericardially applied stem cells was shown (Blázquez et al 2015(Blázquez et al , 2016Branco et al 2009). Further studies are required to investigate the detailed pathway of stem cell homing; there is evidence that inflammation could play an essential role (Zhang et al 2016).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…However, the feasibility of the concept is in line with other recent studies, in which myocardial homing of intrapericardially applied stem cells was shown (Blázquez et al 2015(Blázquez et al , 2016Branco et al 2009). Further studies are required to investigate the detailed pathway of stem cell homing; there is evidence that inflammation could play an essential role (Zhang et al 2016).…”
Section: Discussionsupporting
confidence: 84%
“…To our best knowledge, this is the first study reporting effects of inflammation in terms of a sterile pericarditis on increased myocardial homing. MSC viability, the proliferative behavior and phenotypic pattern, appears unaffected by exposure to pericardial fluid as previously shown (Blázquez et al 2015). Pericardial fluid with a low turnover rate has the potential to serve as therapeutic depot, which allows delivery of high doses of MSCs into pericardial sac.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…121 Also using a very large number (100×10 6 ) of SPION-labeled mesenchymal stem cells delivered by intrapericardial administration in porcine models, the authors identified a significant number of cells retained in the cardiac tissue a few days after injection. 122 In small rodents, it was possible to observe SPION-labeled mesenchymal stem cells (Endorem) after direct injection into the myocardial infarction scar. 123 In our experiments, we also were able to detect SPION-labeled mesenchymal cells after injection of 3×10 6 cells into leg muscle of mice, 15,24 1×10 6 cells into rat striatum, 124 and 5×10 6 rat intravitreally.…”
mentioning
confidence: 99%
“…Local injection in the parenchyma is an invasive method and may lead to further damage to the target tissue . Direct intramyocardial cell delivery developed cardiac arrhythmias and had deteriorating effect on the heart …”
Section: Factors Affecting Cell Fatementioning
confidence: 99%